EFEKTIFITAS KEBIJAKAN PENDIDIKAN KESEHATAN REPRODUKSI PADA ANAK USIA DINI DI PAUD DAN TK KECAMATAN LUBUK BEGALUNG KOTA PADANG - Wilda Tri Yuliza; Febriyanti Nursya (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Reproductive health education in early childhood is a strategic effort to instill an understanding of the body, self-responsibility, and protection against violence and sexual abuse from an early age. The Indonesian government has emphasized the importance of this education through various policies, including the Ministry of Education Regulation No. 84 of 2008 concerning Guidelines for the Implementation of Reproductive Health Education, as well as character education strengthening programs in early childhood education institutions. However, the implementation of these policies still faces several challenges, particularly in terms of teachers’ understanding, institutional readiness, infrastructure support, and cross-sectoral coordination. In Padang City, especially in Lubuk Begalung District, some PAUD and TK institutions have begun introducing reproductive health education, although its implementation remains uneven. This study aimed to analyze the effectiveness of reproductive health education policies for early childhood in PAUD and TK institutions in Lubuk Begalung District, Padang City. The study employed a qualitative approach with a case study design. Informants consisted of principals and teachers from PAUD and TK institutions. Data were collected through in-depth interviews, observations, and document reviews, and were analyzed using data reduction, data presentation, and conclusion drawing techniques. Data validity was ensured through source and technique triangulation.Keywords: Effectiveness, Policy, Reproductive Health Education, Early Childhood.